Analisis Pengaruh Proses Belajar Mengajar dan Fasilitas Pendidikan terhadap Prestasi Belajar Taruna TLB IX di Poltekbang Surabaya - Aulia Regia S.P; R Moh Radix Agustiono (Jurnal Penelitian)
Teaching and learning activities at Aviation Polytechnic of Surabaya are conducted with highly supportive learning facilities, the creation of convenience is the key to improving the quality and results of graduate quality. Adequate classrooms, supportive practice tools, and learning methods that are always updated in accordance with the latest curriculum in the world of aviation are all created for cadets to have competitiveness and competence to compete in the world of work. Result of F Test calculation done with SPSS program is got value of F count equal to 157,135. The value of significance obtained is 0.001, the value of this significance is smaller than the value of a is 0.05. Thus Ho is rejected and Ha accepted, meaning that the independent variables of teaching and learning process (X1) and educational facilities (X2) together affect the variable tied learning achievement (Y) cadet electrical engineering airport force IX at Aviation Polytechnic of Surabaya. In Partial Tests obtained results: For learning process variables / (X1), the value of t arithmetic is 9,464 and the significance value is 0,000, this value is smaller than a = 0,05 thus means that the learning process variables X1) partially has a significant influence on the dependent variable achievement learning (Y) cadet electrical engineering airport force IX at Aviation Polytechnic of Surabaya. For the educational facilities variable / (X2), the value of t arithmetic is 7,913 and the significance value is 0.000, this value is smaller thana = 0,05 so it means that the educational facility variable (X2) partially has significant influence to the variable tied learning achievement (Y) cadet electrical engineering airport force IX at Aviation Polytechnic of Surabaya. From the results of SPSS about partial correlation coefficient, it is known that the variable X1 is the learning process has the highest partial correlation value is 0.832 compared with other independent variables. Therefore, the variable X1 is the variable teaching and learning process is the independent variable that predominantly affects the dependent variable is the learning achievement (Y) cadet electrical engineering airport force IX at Aviation Polytechnic of Surabaya.